Cárie precoce da infância na perspectiva binômio mãe/filho: transmissibilidade de microorganismos ou hábitos de saúde compartilhados? - Costa, Elizabeth Lima (2016)
Introduction: Several risk factors are associated with the ECC, including the S. mutans, identified as responsible for the onset of the disease; maternal saliva, the main source of primary infection to the child, socioeconomic factors, dietary habits and oral hygiene shared in the family environment. Thus, this thesis is divided into two chapters: Chapter I aimed at analyzing the contamination of S. mutans in the mother mediated by the contamination of S. mutans in the child together with the ECC. Chapter II aimed at analyzing the association between the consumption of added sugar by the mother and the frequency of the child's added sugar consumption. Methods: The sample consisted of 697 preschool children between 24 and 71 months old and their mothers. The mothers answered a questionnaire on their general and oral health as well as the child and a food frequency questionnaire (FFQ) to assess the diet of the binomial and the consumption of added sugar by the mother and the child. Mothers and children were subjected to an oral clinical examination to measure the caries index (DMF/ceo), IPV, ISG, anthropometric analysis of the mother's waist circumference and microbiological examination of saliva in 400 mothers / children pairs. A theoretical model based on causal diagrams (DAGs) that allows control of confounding factors in the most appropriate manner and at the same time avoids unnecessary adjustments to mothers / children mediators has been prepared. For Article 1, two models have been suggested, adjusted and analyzed: a total effect model and a mediated effect model of the association between maternal contamination S. mutans and ECC. The Paramed test was used to quantify the proportion of maternal S. mutans contamination effects mediated by contamination by S. mutans in the child in the ECC. To Article 2, two models have been suggested to study the association between the consumption of added sugar by the mother and child: an Effect 1 model and an Effect 2 model. The multinomial regression analysis was used to test the models, based on the DAGs. The marginal structural model was estimated by weighting by the inverse of the probability of consumption exposure in order to assess the association between consumption of added sugar by the mother and child. We estimated the prevalence ratio (PR) and confidence intervals (95% CI), in a 5% significance level. Results: In the total effect model, the presence of high colonization of S. mutans in the mother, the largest measurement of the waist circumference of the mother were associated with the ECC; Maternal IPV; child's age ≥ 4 years old and higher frequency of sugar consumption by the child. In the mediated effect model, the high maternal colonization remained linked to the ECC. Paramed test showed the proportion of mediated effect in 33% of maternal contamination of S. mutans by contamination in the child of S. mutans in the ECC. In effect model 1, the second and third tertile of the mother added sugar consumption was associated with the second tertile of added sugar consumption by the child; likewise the second and third tertile of consumption by the mother were also associated with the third tertile of the child's added sugar consumption. In effect model 2, all these variables of maternal consumption were also associated with the greatest child's consumption tertiles; yet maternal CW ≥88cm was also associated with the highest tertile of sugar consumption by the child. In marginal structural model, the consumption of added sugar by the mother was associated with added sugar consumption by the child. Conclusions: The contamination of S. mutans in the child only partially measured the association of the mother's S. mutans contamination in ECC. Other factors must be considered in the mother/child binomial, such as diet, oral hygiene practices and history of caries in the family environment. Sugar consumption by the mother and the highest maternal metabolic risk seem to explain the child's added sugar consumption in early childhood.